Philippine book of days a calendar of holidays, anniversaries, and festivals - Santos, Minerva E. (Institute of Library Science, University of the Philippines Diliman, 1980)
The Philippine Book of Days is a list, in calendar order, of religious days, patriotic and civic holidays including historical aniiversaries and important events in the Philippines, birth and death anniversaries of notable Filipinos, special observances, and fiestas and festivals in the Philippines. The calendar listing includes a brief discussion about the historical background, and a description of the customs and celebrations, of each observance.